STUDI EVALUASI NILAI DAYA DUKUNG FLOATING PILE BERDASARKAN KOMPARASI DESAIN RENCANA, KALENDERING DAN HASIL UJI PDA TEST PADA PROYEK JEMBATAN DI KABUPANTEN SIDOARJO - Prameswari, Azzuma; Jahja, Annisa Zalsabilla; Estikhamah, Fithri (Civil Engineering Study Program Faculty of Engineering, University of Palembang, 2024)
The foundation is a very important structural element in a building because it serves as an intermediary to transfer loads from the upper structure to the ground. The bearing capacity of the soil is the main factor that determines the foundation's ability to support loads, both from the weight of the building itself and additional loads acting on it. The evaluation of the bearing capacity of floating piles is an important aspect in the design of bridge foundations, especially in areas with complex soil conditions. This study compares three methods of evaluating bearing capacity, namely the Luciano Decourt planning method (1982, 1996), the PDA Test, and Calendarization, to obtain a more holistic picture of pile performance. The research results show that the field test bearing capacity (PDA Test and Calendarization) is significantly higher than the planned capacity. Calendarization provides more stable and consistent values compared to the PDA Test, while the PDA Test shows higher sensitivity to variations in local soil conditions. These results indicate that the combination of the three methods can improve the accuracy in assessing the bearing capacity of the piles.